2020
DOI: 10.1152/ajpregu.00240.2019
|View full text |Cite
|
Sign up to set email alerts
|

Gastric bypass in female rats lowers concentrated sugar solution intake and preference without affecting brief-access licking after long-term sugar exposure

Abstract: In rodents, Roux-en-Y gastric bypass (RYGB) decreases intake of, and preference for, foods or fluids that are high in sugar. Whether these surgically induced changes are due to decreases in the palatability of sugar stimuli is controversial. We used RYGB and sham-operated (SHAM) female rats to test the influence of prolonged ingestive experience with sugar solutions on the motivational potency of these stimuli to drive licking in brief-access (BA) tests. In experiment 1, RYGB attenuated intake of, and caloric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 73 publications
2
12
0
Order By: Relevance
“…After this meal, RYGB animals did not eat again for a long time compared with CTL animals and after resuming food consumption their meals were smaller. This finding is similar to other studies wherein RYGB rats initially responded similarly as control animals in other contexts, such as short-and long-term drinking tests, only to reduce intake in subsequent exposures (e.g., [55,59,60,64,130]).…”
Section: Roux-en-y Gastric Bypass Changes Meal Patterns Primarily By Reducing the Size Of Mealssupporting
confidence: 90%
See 1 more Smart Citation
“…After this meal, RYGB animals did not eat again for a long time compared with CTL animals and after resuming food consumption their meals were smaller. This finding is similar to other studies wherein RYGB rats initially responded similarly as control animals in other contexts, such as short-and long-term drinking tests, only to reduce intake in subsequent exposures (e.g., [55,59,60,64,130]).…”
Section: Roux-en-y Gastric Bypass Changes Meal Patterns Primarily By Reducing the Size Of Mealssupporting
confidence: 90%
“…Many of the basic consequences of RYGB on physiology and behavior in rats emulate those seen in humans; after the surgery both rats and humans lose body weight, have improved glycemic control, reduce intake, and display elevated levels of key gut hormones [18,[51][52][53][54][55][56][57][58][59][60][61]. The changes in the relative intake of energy dense foods and fluids observed in rats after RYGB do not appear to be driven by an unconditioned modulation of the palatability of those foods [18,55,59,60,[62][63][64][65][66]. In fact, the bases of the underlying changes in food selection after the surgery in rats, including whether those changes are tied to the postoral consequences of ingestion, remain unclear.…”
Section: Introductionmentioning
confidence: 98%
“…There are several standard behavioral tests that have been applied in rodent models of BS to assess changes in ingestive behavior. In an ad libitum setting after RYGB, rats show a decrease in intake of calorically dense solutions relative to that of water compared with controls ( 34 36 , 40 ). Moreover, when a vegetable drink was used as an alternative to water and pitted with either fatty or sweet solutions, RYGB rats shifted their preferences to the vegetable drink ( 41 ).…”
Section: Introductionmentioning
confidence: 96%
“…Although the influence of RYGB in humans on food choice and preference is debated, there seems to be consistent evidence for an effect of surgery on diet choice in rodents. Several studies have shown that rats that receive RYGB surgery decrease intake of high-fat or high-sugar food or drink items and/or increase intake of low-fat/-sugar items [50][51][52][53][54][55][56]. Some groups have found decreased hedonic responsiveness to sucrose following RYGB (i.e., assessed in brief-access tests) [57][58][59], but such a surgery-induced influence on taste-related motivational potency of these stimuli is not universally reported [50,54,56,60].…”
Section: Introductionmentioning
confidence: 99%